2006
DOI: 10.1002/cncr.21862
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A is overexpressed in human pancreatic cancer cells and stimulates cell proliferation through CD147

Abstract: BACKGROUNDAlthough overexpression of cyclophilin A (CypA) is associated with several types of cancer, its role in pancreatic cancer has not been studied. In this study the expression of CypA and its receptor CD147 on pancreatic cancer was determined as well as the effect of exogenous CypA on pancreatic cancer cell proliferation.METHODSThe expression of CypA and CD147 in human pancreatic cancer cell lines and tissues was determined with real‐time reverse transcriptase polymerase chain reaction (RT‐PCR), Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(138 citation statements)
references
References 31 publications
6
130
0
2
Order By: Relevance
“…Our studies identified CD147 as an essential component of the cell-surface signaling receptor to CypA and CypB [10;11;13]. This notion has been supported in a number of subsequent publications [14][15][16]. CypA is incorporated into HIV-1 particles during virus morphogenesis through a specific interaction with the CA domain of the Gag precursor polyprotein [17][18][19][20] and plays an essential role in the early steps of the HIV-1 life cycle [21;22].…”
Section: Introductionsupporting
confidence: 69%
“…Our studies identified CD147 as an essential component of the cell-surface signaling receptor to CypA and CypB [10;11;13]. This notion has been supported in a number of subsequent publications [14][15][16]. CypA is incorporated into HIV-1 particles during virus morphogenesis through a specific interaction with the CA domain of the Gag precursor polyprotein [17][18][19][20] and plays an essential role in the early steps of the HIV-1 life cycle [21;22].…”
Section: Introductionsupporting
confidence: 69%
“…Upregulation of CypA or CypB has been found in primary human cancers. 34,[36][37][38][39][40] In some cases, this upregulation has been associated with enhanced metastasis, radioresistance and poor clinical prognosis. 41,42 Although the direct correlation between expression of cyclophilins and phosphorylation of p38MAPK has not been established, increased levels of phosphorylated p38MAPK have been described in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…α-enolase is a plasminogen-binding protein and also appears to play a major role in the promotion of plasminogen activation by leukocytic cells [74]. Peptidylprolyl isomerase (cyclophilin A) has been associated with a number of cancer histiotypes including breast [75] and pancrease [76,77], and has been implicated in cellular resistance to hypoxia-and Cisplatininduced cell death [78] and resistance to aplidin [79]. Its secretion from regressive tumor masses has been previously been studied by MS [80] and it has been profiled as one of a number of glycolytic enzymes increased in pancreatic cancerous tissues [76].…”
Section: Non-classical Secretionmentioning
confidence: 99%